2021
DOI: 10.1038/s41467-021-27386-2
|View full text |Cite
|
Sign up to set email alerts
|

Thawing Yedoma permafrost is a neglected nitrous oxide source

Abstract: In contrast to the well-recognized permafrost carbon (C) feedback to climate change, the fate of permafrost nitrogen (N) after thaw is poorly understood. According to mounting evidence, part of the N liberated from permafrost may be released to the atmosphere as the strong greenhouse gas (GHG) nitrous oxide (N2O). Here, we report post-thaw N2O release from late Pleistocene permafrost deposits called Yedoma, which store a substantial part of permafrost C and N and are highly vulnerable to thaw. While freshly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(103 citation statements)
references
References 75 publications
10
92
1
Order By: Relevance
“…Collembola presence modified bacterial communities in newly thawed permafrost and primed its CO 2 production, highlighting the importance of non-microbial decomposers for the fate of soil organic matter in thawing permafrost. An emerging theme in permafrost research is the missing functions in permafrost microbial communities due to a lack of certain microbial groups, hampering the production of CO 2 , CH 4 and N 2 O (Knoblauch et al, 2018;Monteux et al, 2020;Marushchak et al, 2021). It is also becoming clearer that the functionality of permafrost microbes can vary across space (Barbato et al, 2022); therefore the modalities of microbial dispersal into newly thawed permafrost likely affect the fate of the permafrost's organic matter and the rate of release of greenhouse gases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collembola presence modified bacterial communities in newly thawed permafrost and primed its CO 2 production, highlighting the importance of non-microbial decomposers for the fate of soil organic matter in thawing permafrost. An emerging theme in permafrost research is the missing functions in permafrost microbial communities due to a lack of certain microbial groups, hampering the production of CO 2 , CH 4 and N 2 O (Knoblauch et al, 2018;Monteux et al, 2020;Marushchak et al, 2021). It is also becoming clearer that the functionality of permafrost microbes can vary across space (Barbato et al, 2022); therefore the modalities of microbial dispersal into newly thawed permafrost likely affect the fate of the permafrost's organic matter and the rate of release of greenhouse gases.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all microbes survive these conditions, and the combination of environmental constraints exerted over long periods of time (Mackelprang et al, 2017) and strong dispersal limitations (Bottos et al, 2018) results in microbial communities that can be deprived of some functions (Knoblauch et al, 2018;Monteux et al, 2020;Barbato et al, 2022). The re-introduction of such functions can result in drastic changes in permafrost processes, and sizable impacts on greenhouse gas production have been observed in vitro for CH 4 and CO 2 (Knoblauch et al, 2018;Monteux et al, 2020) and confirmed in situ for N 2 O (Marushchak et al, 2021). Upon thawing, this re-introduction of missing functions or ecological rescue (Calderón et al, 2017) requires microorganisms to migrate into this newly available habitat, which could happen for instance laterally through airborne dispersal (Harding et al, 2011) -e.g.…”
Section: Introductionmentioning
confidence: 90%
“…We expect this to be particularly pronounced for metabolic processes that have narrow phylogenetic breadth—that is, where functional guild members (microorganisms sharing a metabolic trait) are phylogenetically clustered—as there is a greater potential for stochastic processes to remove that entire function. For example, methanogens and nitrifiers are phylogenetically narrow guilds, and even under suitable environmental conditions, the absence of methanogens can limit CH 4 production (Figure 2, Example 1; Ernakovich et al, 2017; Knoblauch et al, 2018, 2021) and the absence of ammonia oxidizers can limit N 2 O production rates (Figure 2, Example 2; Alves et al, 2019; Siljanen et al, 2019; Monteux et al, 2020; Marushchak et al, 2021). Stochastic factors are particularly impactful for phylogenetically and ecologically constrained guilds (Vellend, 2010).…”
Section: Space and Time Direct Deterministic Versus Stochastic Assemblymentioning
confidence: 99%
“…Warming has been shown to alleviate limitations on N 2 O production (Salazar et al, 2020), indicating that deterministic processes (i.e., environmental filtering) could become increasingly important following thaw. Indeed, Marushchak et al (2021) found that shortly after thaw, N 2 O flux was limited, but that within a few years N 2 O rates can increase rapidly concomitant with increasing nitrifier abundance. Functional guilds contributing to N 2 O flux are ecologically, and possibly even phylogenetically, narrow in cold regions.…”
Section: The Cumulative Effects Of Assembly Processes Affect Function...mentioning
confidence: 99%
“…Traditionally, it has been suggested that N 2 O emissions from arctic soils are negligible because of the low concentrations of mineral N in soils underlain by permafrost (Ma et al, 2007;Takakai et al, 2008;Siciliano et al, 2009;Goldberg et al, 2010). However, this generalization has been challenged by the identification of hotspots of N 2 O on raised permafrost peatlands (Repo et al, 2009;Marushchak et al, 2011) and by measurements of high N 2 O concentrations (Abbott and Jones, 2015) and high N 2 O emissions (Marushchak et al, 2021) in mineral tundra soils following permafrost thaw. A field warming experiment in a permafrost peatland further showed that soil warming (average increase of 0.95 • C) promotes N 2 O release not just from bare peat (BP) hotspots but also from adjacent vegetated surfaces that do not emit N 2 O under the present climate (Voigt et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%